A Stereophonic Acoustic Echo Cancellation Algorithm Based on Sub-band Extended LMS Algorithm and Dual-Filter Structure - Xiao, Zeping; Zhou, Yi; Ma, Yongbao; Liu, Hongqing (2022 IEEE 8th International Conference on Computer and Communications (ICCC), 2022)
Acoustic Echo Cancellers are widely used in speech communication applications to cancel echoes that result from the coupling between loudspeaker and microphone. Nowadays many teleconferencing systems use two-channel audio to enhance sound realism. However, stereophonic acoustic echo cancellation (SAEC) is more difficult than its single-channel counterpart because of the high correlation between the two excitation signals. This paper proposes a SAEC algorithm with excellent convergence performance and robust double talk detection (DTD) performance, which uses an Extended LMS (ELMS) algorithm in sub-bands. By utilizing the dual-filter structure with a robust transfer logic, the proposed algorithm becomes more stable in a double-talk situation. The experimental results prove that the proposed SAEC algorithm outperforms the sub-band ELMS algorithm with pseudo-coherence and ELMS algorithm with pseudo-coherence based on block processing in frequency-domain (two-channel FLMS).